Vitamin E D‐alpha‐tocopheryl polyethylene glycol 1000 succinate‐conjugated liposomal docetaxel reverses multidrug resistance in breast cancer cells. (18th June 2019) - Li, Na; Fu, Tingting; Fei, Wenling; Han, Tianyan; Gu, Xiangshuai; Hou, Yanhui; Liu, Yanhua; Yang, Jianhong
Abstract: Objectives: Multidrug resistance (MDR) remains a primary challenge in breast cancer treatment. In the present study, D‐alpha‐tocopheryl polyethylene glycol 1000 succinate (TPGS)‐coated docetaxel‐loaded liposomes were developed as a novel drug delivery system to reverse MDR and enhance breast cancer therapy compared with the traditional liposomes, DSPE‐mPEG‐coated liposomes (stealth liposomes) and commercial Taxotere ® . Key findings: Liposomes were prepared by thin – film dispersion method. Evaluations were performed using human breast cancer MCF‐7 and resistant MCF‐7/ADR cells. The reversal multidrug‐resistant effect was assessed by P‐gp inhibition assay, cytotoxicity, cellular uptake and apoptosis assay. Results: The TPGS‐chol‐liposomes were of an appropriate particle size (140.0 ± 6.0 nm), zeta potential (−0.196 ± 0.08 mv), high encapsulation efficiency (99.0 ± 0.9) and favourable in vitro sustained release. The TPGS‐coated liposomes significantly improved cytotoxicity and increased the intracellular accumulation of docetaxel in both types of breast cancer cells. The TPGS‐coated liposomes were confirmed to induce apoptosis via a synergistic effect between docetaxel and TPGS. It was demonstrated that TPGS enhanced the intracellular accumulation of drug by inhibiting overexpressed P‐glycoprotein. Conclusions: The TPGS‐conjugated liposomes showed significant advantages in vitro compared with the PEG‐conjugated liposomes. The TPGS‐conjugated liposomes could reverse the MDR and enhance breast cancer therapy.